Comparison of delinquent children with single and repeated criminal behavior in terms of various variables - Gürbüz Özgür, Börte; Manav Diril, Rabia Gizem; Tatlı, Şeyma; Aksu, Hatice (The Bulletin of Legal Medicine, 2025)
Objective: Determining risk factors in juvenile delinquents (JD) has gained significance in preventive psychiatry. This study aims to assess the sociodemographic and clinical characteristics of JD and to determine whether there are differences in the various variable comparisons between single and repeat offender children.Methods: The data of a total of 256 JDs cases out of 1350 forensic cases who underwent forensic examination at a university hospital’s child and adolescent psychiatry outpatient clinic between 2013 and 2023 were included. Results: The mean age at the time of the first crime for 256 JDs was 14.04±1.28, with 44 (17.2%) exhibiting recurrent criminal behavior. Recurrent criminal behavior group had a higher rate of accompanying psychopathology compared to the group with single criminal behavior (p=0.009). In the group with recurrent crimes, statistically significant higher rates of school absenteeism (p
Keywords: Forensic Psychiatry; Child; Juvenile Delinquency; Risk Factors; Crime